(untitled) - Tel, Gerard (Cambridge UK, 2000)
The second edition of this successful textbook provides an up-to-date introduction both to distributed algorithms and to the theory behind them. The clear presentation makes the book suitable for advanced undergraduate or graduate courses, while the coverage is sufficiently deep to make it useful for practicing engineers and researchers.
Keywords: Computer algorithms,Xử lý dữ liệu điện tử,Electronic data processing,Thuật toán; Phân phối máy tính,Distributed processing